A Study of q-Deformed Bosons, and Their Implications to Quantum Optics - Senay, Mustafa; Şenay, Mustafa (Sakarya University, 2024)
In this study, we investigate three types of q-deformed boson oscillators, focusing on their mathematical frameworks and thermodynamic properties. We calculate key thermodynamic quantities, such as internal energy and entropy, as functions of the deformation parameter q. Our results reveal that these oscillators are eigenstates of specific deformed boson annihilation operators. We also analyze their unique characteristics and implications in deformed quantum optics. Furthermore, we examine the impact of q-deformation on qutrit logic gates, including cycle, self-shift, controlled cycle, controlled self-shift, Feynman, ternary Toffoli, and Fredkin gates, highlighting their altered computational properties. This research contributes to a deeper understanding of q-deformed systems and their applications in quantum computing. Overall, it opens new avenues for exploring the interplay between deformation parameters and quantum information processing. © 2025 Elsevier B.V., All rights reserved.
A Study of q-Deformed Bosons, and Their Implications to Quantum Optics
Keywords: Q-Deformed Boson; Quantum Optics; Quantum Statsitics; Thermodynamics